Dynamics of Contract Design with Screening - Cvitanić, Jakša; Wan, Xuhu; Yang, Huali (Management Science, 2013)
We analyze a novel principal–agent problem of moral hazard and adverse selection in continuous time. The constant private shock revealed at time 0 when the agent selects the contract has a long-term impact on the optimal contract. The latter is based not only on the continuation value of the agent who truthfully reports but is also contingent upon the continuation value of the agent who misreports, called the temptation value. The good agent is retired when the temptation value of the bad agent becomes large, because then it is expensive to motivate the good agent. The bad agent is retired when the temptation value of the good agent becomes small, because then the future payment does not provide sufficient incentives. We also compare the efficiency of the shutdown contract and the screening contract and find that the screening contract can bring more profit to the principal only when the agent's reservation utility is sufficiently small. This paper was accepted by Wei Xiong, finance.